2000
DOI: 10.1046/j.1469-8137.2000.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Beetle grazing reduces natural infection of Rumex obtusifolius by fungal pathogens

Abstract: In previously reported laboratory experiments, infection of Rumex obtusifolius by the rust fungus Uromyces rumicis was decreased on leaves which had prior herbivory by the beetle Gastrophysa viridula. In this paper we investigate whether this interaction is robust for natural infection by a variety of fungi in field experiments carried out in spring and autumn with plants given different levels of nitrogen fertilization. Grazing by G. viridula led to a decrease in lesion density of Ramularia rubella and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…attacked by the leaf beetle Gastrophysa viridula and the biotrophic rust fungus Uromyces rumicis. Hatcher and co-workers (Hatcher et al, 1994a(Hatcher et al, ,b, 1995Hatcher and Paul, 2000) found that fungus infection made Rumex plants less preferred for oviposition and consumption by the beetle and, vice versa, that plants subjected to leaf beetle damage were less prone to rust infection. The studies reviewed by Rostàs et al (2003) showed a general tendency of adverse effects of plant antagonists on each other.…”
Section: Cross-effectsmentioning
confidence: 99%
“…attacked by the leaf beetle Gastrophysa viridula and the biotrophic rust fungus Uromyces rumicis. Hatcher and co-workers (Hatcher et al, 1994a(Hatcher et al, ,b, 1995Hatcher and Paul, 2000) found that fungus infection made Rumex plants less preferred for oviposition and consumption by the beetle and, vice versa, that plants subjected to leaf beetle damage were less prone to rust infection. The studies reviewed by Rostàs et al (2003) showed a general tendency of adverse effects of plant antagonists on each other.…”
Section: Cross-effectsmentioning
confidence: 99%
“…Both factors decrease leaf N content, increase leaf C and water content and additively raise leaf consumption by G. viridula (Hatcher 1995, 1997a. However, previous herbivory reduces the infection of Rumex leaves by U. rumicis (Hatcher et al 1994, Hatcher andPaul 2000). Air CO 2 content that is expected to increase may also influence leaf acceptability (Pearson andBrooks 1996, Brooks and.…”
Section: G Viridula In Dock Biocontrolmentioning
confidence: 99%
“…A similar type of interaction could be important on roofs where herbivorous beetles could help reduce establishment of tree seedlings that can lead to waterproof membrane puncture and roof failure; yet, no granviores and a much lower percentage of herbivores in general were found on stormwater roofs. Another study found that grazing on an herbaceous plant by a specialist beetle limited the establishment of the plant's fungal pathogen (Hatcher and Paul 2000). If the increased functional diversity demonstrated in this study leads to similar interactions this could result in a desirable reduction in maintenance needs on green roofs.…”
Section: Functional Diversitymentioning
confidence: 57%